Mitogenomic phylogeny of Cypraeidae (Gastropoda: Mesogastropoda) - Ma, Qingxia; Li, Fengping; Zheng, Jiawen; Liu, Chunsheng; Wang, Aimin; Yang, Yi; Gu, Zhifeng (Frontiers in Ecology and Evolution, 2023)
Cowries (Family Cypraeidae) are widely distributed in tropical and subtropical seas, with the highest diversity of cowries in the Indo-Pacific region. However, the classification of Cypraeidae, especially at the lower taxonomic levels, is still controversial. In the present study, we determined the complete mitochondrial genomes of 10 cowries. All the newly sequenced mtDNA encode 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, 2 ribosomal RNA (rRNA) genes and several non-coding regions. The reconstructed mitogenomic phylogeny of Cypraeidae recognized two monophyletic clades that corresponed to different shell size. The first clade comprised of Erroneinae, Cypraeinae and Luriinae are characteristic with a medium to large size of shell, while the second clade formed by the single subfamily Erosarinae possesses a small shell size. The two different shell size was found to be related to distinct distribution patterns, therefore suggesting an environmental adaption. The congeneric genetic distance values fall within 0.118-0.144, lower than those above genus level ranging from 0.163 to 0.271, consistent with the current division of genera within Cypraeidae. The divergence time estimated here indicated that the ancestor of Indo-Pacific cowries diversified during the Paleocene, and the closure of the Tethys Seaway might lead to the speciation events of several Indo-Pacific species. This study suggests that the complete mtDNA is a promising tool to improve the phylogenetic resolution of Cypraeidae, and mtDNA could also provide important information for future species delimitation especially within the cowries that possess different morphological phenotypes.